The Effect of Artificial Feeding Treatments on Predatory and Pollinating Ants in Cayenne Pepper Plants - Tamrin Abdullah; Melina Melina; Prihatin Prihatin; Nurul Wiridannisaa; A. Dian Ridha Maghfirah (Jurnal Biologi Tropis, 2023)
Pests have the potential to reduce the quality and quantity of cayenne pepper production. Pest control is done by utilizing natural enemies, such as ants by being stimulated with artificial food. This study aims to observe the population of dominant species and the effect of various artificial feeding treatments on ants that act as predators or pollinators in chili plants. The study was arranged in a Randomized Group Design (RGD) with 5 treatments, namely P0: Control (no pellet or sugar solution treatment); P1: 10 g artificial feed pellets; P2: 10% sugar solution; P3: 10% sugar solution and 10 g artificial feed pellets; and P4: 10 g artificial feed pellets (put into artificial nest) which was repeated 4 times.  Observations were made five times at three-day intervals. Data were analyzed by calculating the species diversity index (H'), species dominance index (C), and ant population. Based on the results, the ant diversity index in this experiment was classified as moderate at 1.17 (H' 1.0-3.0) and the ant dominance index was 0.35 (low: C<0.5). Ant identification revealed four species from three sub-families: Myrmicinae, Dolichodorinae, and Formicinae, namely Pheidole sp., Monomorium sp., Tapinoma sp., and Paratrechina sp. While species that have the potential as predators or pollinators on chili plants are Tapinoma sp.. Artificial feeding with treatment P3 (10 g artificial feed and 10% sugar solution) can have an effect and increase the population of Tapinoma sp. ants with an average of 81.95 heads on chili plants.